Performance, Carcass Characteristics, and Meat Quality of Broiler Chickens Fed β-Mannanase and Two Levels of Energy - M. A. R. Jalal; H. A. H. Zakaria; F. M. Hayajneh; G. M. Mehyar (Tropical Animal Science Journal, 2023)
This study aimed at evaluating the response to supplementation of β-Mannanase with two levels of energy on performance, carcass yield, and meat quality of 1600 1-d-old straight run Indian River broilers which were randomly allotted to 4 dietary treatments (10 replicates/treatment, 40 chicks per replicate) in a 35-d feeding trial. The trial consisted of 2 phases, starter (0 to 14 d) and grower (15 to 35 d). The experiment was designed in a 2 x 2 factorial arrangement. The first factor was the energy level of the ration consisted of 2 levels, i.e., a low energy level with 2.900 kcal ME/kg during the starter phase and 3.000 kcal ME/kg during the grower phase; and a normal energy level with 3020 kcal ME/kg during starter phase and 3120 kcal ME/kg during grower phase, with variations based on the content of feed grade soybean oil. The second factor was the level of β-Mannanase in the diet consisted of 2 levels, i.e., ration without β-Mannanase (BETAMINUS: 0%) and ration with 0.05% β-Mannanase (BETAPLUS: 0.05%). Feeding low ME increased feed intake (p<0.05) during the overall phase (0 to 35 d) and normal ME decreased (p<0.05) feed conversion ratio during the starter and overall phases. Birds fed normal ME exhibited higher (p<0.05) hot and cold carcass weights. There was a significant interaction between dietary ME level and β-Mannanase to breast meat pH (p= 0.006), meat redness (a*) (p= 0.01), and meat yellowness (b*) (p= 0.0001). In conclusion, the results of enzyme supplementation did not elicit any noticeable response pertaining to productive performance, carcass characteristics, or meat quality (except pH and meat color). Moreover, feeding low dietary ME and β-Mannanase did not compromise overall broiler chickens performance.